Rock bottom - Michaels, Fern (Michaels, Fern. Sisterhood, 2023)
As the world's most famous vigilantes, the women of the Sisterhood have seen justice served countless times over the years. When an old classmate of one of the members of the Sisterhood suspects that her firm's foundation materials may be the reason a number of bridges and buildings have been collapsing, it is time for the Sisterhood to go into action. But this adversary has money, power, and resources to match the Sisterhood's--and no intention of giving up without a fight.